Model Organisational Structure of the Kulliyatul Mu’allimin Al-Islamiyah Curriculum Content - Taufik Mukmin; Abdurrahmansyah Abdurrahmansyah; Aflatun Muchtar; Yesi Arikarani (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to analyse the design and structure of the content, the type of knowledge that is arranged in the form of subjects, and the content of knowledge in each subject. This research uses qualitative research with phenomenological types, data collected through in-depth interviews, observation and documentation, as well as analysing data through reduction, display and conclusion. The results show that the Kulliyatul Mu’allimin Al-Islamiyah (KMI) content organisation model is "Eclectic" or a combination of several existing curriculum models. On the one hand, adopting the "Correlated Subject" model, namely by grouping all subjects into three main groups, namely 1) the Islamic science group (al-ulum al-islamiyah), 2) the linguistics group (al-ulum al-lughawiyah) and 3) general knowledge group (al-ulum al-’ammah). And the lessons in each group are correlated with each other. However, in terms of its application, it adopts the "Separated Subject" model where each subject from the group of disciplines is taught separately.